Analysis of Patient Satisfaction at Outpatient Installation in the Hospitals: A Systematic Literature Review - Bayu Subagja; Rosyidah Rosyidah (Universitas Ahmad Dahlan, 2023)
Background: A hospital is a public facility that offers services to improve individual health status. One of the services offered by the hospital is an outpatient installation. As healthcare institutions, hospitals need to optimize their quality to ensure patient satisfaction with outpatient services. Method: This research is a systematic literature review that contains reviews of several studies using the PRISMA method. Related articles carry out by https://sinta.kemdikbud.go.id/journals/index/page. Inclusion criteria are the research articles must be published between the years 2018-2023, journals indexed by SINTA 1 or 2, and research subjects who were undergoing outpatient care at hospitals in Indonesia. There were 6 research articles that were close to the inclusion criteria and were determined to be the study material in this study. Results: The results of studies found that the quality of hospital services significantly influences the level of patient satisfaction. The dimensions of satisfaction including tangible, reliability, assurance, responsiveness, and empathy have a significant influence on patient satisfaction, so hospital management should be able to fulfill the five dimensions of satisfaction. Efforts can be made to improve quality by identifying indicators of patient expectations and needs regarding comfort when accessing outpatient services at hospitals Conclusion: Assessment of patient needs can be evaluated by satisfaction surveys or by providing compliant services centers. Thus, the patient's expectations can be used as an improvisational study in optimizing available facilities, the reliability, and responsiveness of officers, as well as the attitude shown by officers toward outpatients at the hospital.